Respuesta :

Answer:

Option C. -8

Step-by-step explanation:

They ask us to find

(fof)(0)

To solve this problem we must introduce the function f(x) within the function f(x)

That is, we must do g(f(x)).

So, we have:

f(x) = 3x-2

Then:

f(f(x)) = 3(3x-2)-2

This is:

f(f(x)) = 9x-6 -2

f(f(x)) = 9x-8

Now we must do x = 0

f(f(0)) = 9(0) -8

(fof)(0)  = -8

The answer is: option c (fof)(0) = -8.

Answer:

Choice c is correct answer.

Step-by-step explanation:

We have given a function.

f(x) = 3x-2

We have to find the composition of function to itself.

(fof)(x) = ?  and (fof)(0) = ?

(fof)(x) = f(f(x))

Putting values in above formula, we have

(fof)(x) = f(3x-2)

(fof)(x) = 3(3x-2)-2

(fof)(x) = 9x-6-2

(fof)(x) = 9x-8

Putting x = 0 in above equation, we have

(fof)(0) = 9(0)-8

(fof)(0) =  0-8

(fof)(0) =  -8 which is the answer.

ACCESS MORE